Atypical sympathetic arousal in children with autism spectrum disorder and its association with anxiety symptomatology - Sakeena Panju; Jessica Brian; Annie Dupuis; Evdokia Anagnostou; Azadeh Kushki (2015)
Autism spectrum disorder (ASD) has been associated with autonomic atypicalities, although the nature of these differences remains largely unknown. Moreover, existing literature suggests large variability in autonomic function in ASD, motivating the need to examine the existence of subgroups that exhibit more homogeneous autonomic features.Electrodermal activity (EDA), a non-invasive physiological indicator of autonomic activity, was measured in typically developing children (n = 33) and those with ASD (n = 38) as participants performed tasks that elicit anxiety, attention, response inhibition, and social cognition processes. The ASD group was divided into low- (n = 18) and high-anxiety (n = 20) participants, and the groups were compared to mean EDA level and electrodermal reactions frequency (EDR).The ASD group had a significantly blunted mean EDA response to the anxiety tasks (p < 0.004). The EDR response to all tasks, except response inhibition, was also blunted in the ASD group (p < 0.04). For this group, EDR frequency during the anxiety and social cognition tasks was negatively correlated with behavioral scores in the domains that were probed by each task (p < 0.002). The high-anxiety ASD group showed significantly decreased mean EDA compared to both the low-anxiety ASD group (p = 0.02) and the typically developing control group (p = 0.04). The high-anxiety ASD group also had significantly more severe symptoms than the low-anxiety ASD group on domains related to anxiety, attention, rule breaking, aggression, obsessions and compulsions, and depression.Our results suggest atypical autonomic function in children with ASD, specifically with respect to sympathetic activity. Moreover, anxiety symptomatology defined subgroups with distinct physiological and behavioral profiles. Overall, the results add to the body of literature supporting autonomic dysfunction in ASD and highlight the role of anxiety and autonomic features in explaining the variability in the autism spectrum.